PENGARUH GOOD CORPORATE GOVERNANCE, KEPEMILIKAN KELUARGA DAN KEPEMILIKAN INSTITUSIONAL PADA BIAYA EKUITAS PERUSAHAAN MANUFAKTUR - Amelia, Viona Rizqi; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of good corporate governance, family ownership and institutional ownership against the cost of equity. The sample used in this study amounted to 165 companies manufacturing sub-sectors of basic industry and chemical listed in 2010-2014. The data analysis technique used in this research is multiple linear regression analysis. Based on the analysis a significant negative effect of good corporate governance to the cost of equity, positive significant effect of family ownership against the cost of equity, and a significant negative effect on the cost of institutional ownership of equity.
Keywords: GCG, Family Ownershi, Institutional Ownership and Cost of Equity